Outcomes of standard dose EC‐MPS with low exposure to CsA in DCD renal transplantation recipients with DGF. (May 2015) - Ding, C.; Xue, W.; Tian, P.; Ding, X.; Pan, X.; Yan, H.; Xiang, H.; Feng, X.; Hou, J.; Tian, X.; Li, Y.; Zheng, J.
Summary: Aims: The lower limit of exposure to cyclosporine A (CsA) has not yet been established in donation after cardiac death (DCD) renal transplantation recipients with delayed graft function (DGF) receiving enteric‐coated mycophenolate sodium (EC‐MPS) therapy. Stable and adequate mycophenolic acid (MPA) dosing may facilitate lower CsA exposure after DCD renal transplantation in recipients with DGF without compromising safety. Methods: A 12‐month, single‐centre open‐label prospective trial was performed in our centre. According to their DGF risk index using the previous DGF prediction models, we divided up the patients on oral CsA into either a DGF group ( n  = 26) and no DGF group ( n  = 48). All of the patients initially received the standard EC‐MPS dosing (1440 mg/day). The initial dose of CsA in the low risk of DGF group was 4.5 mg/kg/day and in the high risk of DGF group was 2.5 mg/kg/day. Efficacy parameters, safety and tolerability were assessed over a 12‐month study period. Results: The incidence of DGF was 18.5% in the 162 DCD recipients. Between the DGF group and the no DGF group, the 1‐year patient survival and graft survival were not significantly different. The incidence of BPAR was higher in the DGF group (26.9% vs. 8.3%, p = 0.032). Most patients in the DGF group had recovery of renal function after 1 month. The adverse events between the two groups were not significantly different. The daily EC‐MPS doses of the DGF group were significantly higher than the no DGF group before the 6‐month follow‐up period. There were no significant differences between the two groups regarding the mean AUC levels during the follow‐up period. Conclusions: These results show that low expose CsA with standard dosing of EC‐MPS and thymoglobulin was efficacious, safe and well‐tolerated in DCD renal transplant recipients with DGF in China. Furthermore, stable and adequate MPA exposure helped to reduce the dose of and exposure to CsA. Thus, this may lead to less‐induced nephrotoxicity and better renal function recovery.